Tadbir Da'wah Managing Trust and Credibility in Digital Risk Society - Hamriani Hamriani; M Hidayat (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2026)
This study examines how cyber risks and digital uncertainty shape preacher credibility, audience selectivity, and digital trust in social media based da'wah practices. Employing qualitative netnography and digital risk analysis, data from user comments, audience responses, and verification practices were analyzed thematically through risk society theory, communication systems theory, and ilmu dakwah, particularly tadbir da'wah. Findings indicate that digital da'wah operates as a networked discursive space in which the five constitutive elements of da'wah are structurally reconfigured by algorithmic mediation and fragmented authority. Digital trust functions as a complexity reducing mechanism sustaining communicative legitimacy amid informational uncertainty, while preacher and audience adaptation operationalizes tadbir da'wah management functions empirically. This study contributes to ilmu dakwah by repositioning cyber risk as an integral managerial dimension of digital preaching, proposing tabayyun as an epistemological principle for digital trust governance, and reimagining tadbir da'wah as credibility and symbolic legitimacy governance within networked da'wah ecosystems.